Characteristics of urban housing units and their relation to the economic and social characteristics of their residents - A field study on the city of Mosul - al-Doji, Mumtaz Hazem (Iraqi Journal of Architecture and Planning, 2009)
Iraqi cities have a rapid growth in their urban area with explosive population increase. This growth is accompanied with advent of various residential pattems. The phenomenon is conspicuously explicit in Mosul as the major urban center in the north region of Iraq. The hypothesis which states that residential pattems -by means of their physical features and location within urban area- are correlated with the occupants’ characteristics including demographic, socio-economic, ethnic, cultural . . etc. is adopted and to be tested in order to determine the nature and scope ofthis relationship in Mosul.